2004
DOI: 10.1002/jca.20030
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell mobilization in multiple myeloma patients: Do we need an age‐adjusted regimen for the elderly?

Abstract: The upper age limit for autologous progenitor cell transplantation in multiple myeloma patients is increasing continuously. We examined whether this shift in the age of pretreated myeloma patients requires modification of mobilization regimen. We compared retrospectively 21 consecutive progenitor cell mobilizations in 15 pts < 60 years (median age 56, range 37-59) with 33 consecutive mobilizations in 23 pts > 60 years (median age 65, range 60-73) of age. The number of CD34 positive circulating cells before sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16] However, the value of patient characteristics and prior treatment clinical factors to successfully score and accurately predict the risk of poor mobilization is controversial, and recent studies do suggest that they are inaccurate predictors and should not be used to identify candidates for optimized strategies to prevent mobilization failure. 17,18 At present, the measurement of preapheresis levels of CD34+ cells in PB 7,[19][20][21][22] is the most robust and recommended indicator to identify potential poor mobilizers and efficiently rescue them with novel mobilization strategies, including the use of plerixafor.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] However, the value of patient characteristics and prior treatment clinical factors to successfully score and accurately predict the risk of poor mobilization is controversial, and recent studies do suggest that they are inaccurate predictors and should not be used to identify candidates for optimized strategies to prevent mobilization failure. 17,18 At present, the measurement of preapheresis levels of CD34+ cells in PB 7,[19][20][21][22] is the most robust and recommended indicator to identify potential poor mobilizers and efficiently rescue them with novel mobilization strategies, including the use of plerixafor.…”
Section: Introductionmentioning
confidence: 99%
“…Primary mobilization failure occurs in 5-40% of patients. [5][6][7][8][9] Risk factors for poor mobilization include older age, 10 prior radiation therapy, extensive prior chemotherapy, exposure to lenalidomide or purine analogues and extensive BM involvement by malignancy. [11][12][13] Options for those patients who fail to mobilize are limited.…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors directly affecting the feasibility of these procedures is the mobilization capacity of CD34+ cells. The available data are contradictory because several studies have demonstrated that mobilization capacity is poorer in elderly patients compared with younger patients [15][16][17][18][19]. Of our 359 patients, the success of the mobilization procedure was similar between younger and older patients: 90.6% versus 92%, respectively.…”
Section: Discussionmentioning
confidence: 79%